Design and test of stem diameter inspection spherical robot - Quan, Longzhe; Chen, Ci; Li, Yajun; Qiao, Yajing; Xi, Dejun; Zhang, Tianyu; Sun, Wenfeng (International Journal of Agricultural and Biological Engineering, 2019)
Stem diameter is an important parameter in the process of plant growth which can indicate the growth state and moisture content of the plant, its automatic detection is necessary. Traditional devices have many drawbacks that limit their practical uses in general case. To solve those problems, a stem diameter inspection spherical robot was developed in this study. The particular mechanism of the robot has turned out to be suitable for performing monitoring tasks in greenhouse mainly due to its spherical shape, small size, low weight and traction system that do not produce soil compacting or erosion. The mechanical structure and hardware architecture of the spherical robot were described, the algorithm based on binocular stereo vision was developed to measure the stem diameter of the plant. The effectiveness of the prototype robot was confirmed by field experiments in a tomato greenhouse. The results showed that the machine measurement data was linearly correlated with the manual measurement data with R2 of 0.9503. There was no significant difference for each attribute between machine measurement data and manual measurement data (sig > 0.05). The results showed that this method was feasible for nondestructive testing of the stem diameter of greenhouse plants.Keywords: stem diameter inspection, spherical robot, binocular stereo vision, Census transformDOI: 10.25165/j.ijabe.20191202.4163Citation: Quan L Z, Chen C, Li Y J, Qiao Y J, Xi D J, Zhang T Y, et al. Design and test of stem diameter inspection spherical robot. Int J Agric & Biol Eng, 2019; 12(2): 141–151.